Komodifikasi Identitas Konsumsi Sepatu Adidas Adizero EVO SL pada Komunitas Pelari Palembang: Kajian Simbolik Budaya Lari - Pahalmas, Juniior Zamrud; Pratiwi, Diany Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
Today, runners are not only pursuing a contextual pursuit of health, but also many efforts to build self-image through social media. Between the ubiquitous personal branding and becoming an urban lifestyle, running now provides a reflection and response to the increasingly dense and stressful urban conditions. This shows how a commodity (running shoes), not only functions practically, but also undergoes a process of identity commodification, when individual or group identities are formed, represented, or even sold through consumer products. The Adidas Adizero EVO SL shoes are more than just footwear, but also a symbol and status, membership of a particular community, to a representation of ideal self-performance according to the construction of popular culture. From this, we can see how the concept of identity commodification is strongly visible. The identity of a runner is not only shaped by physical activity, but also from the ownership and appearance of certain products, including the phenomenon of the Adidas Adizero Evo SL. The approach of identity commodification theory, it is important to examine how the Adidas Adizero EVO SL is commodified as a cultural symbol and how runners as consumers interpret this product in the formation of their identities. This research is relevant to understanding how consumption practices in running culture reflect broader social dynamics related to social class, symbolism, and identity mediation in contemporary society. The analysis concludes that the Adidas Adizero EVO SL shoes in the Palembang running community are not merely consumer goods, but rather symbols rich with meaning. This consumption practice reflects the process of identity commodification, where runners' identities are constructed and traded through products and the operationalization of the concepts of habitus, capital, and distinction. This research can serve as a reference for expanding research that can be conducted in running communities in other cities to examine how global sportswear products are consumed.